Analysis of BRT Infrastructure in Jakarta Province on Women's Perspective - Sunandar, Ali; Ainundyasari, Aprillia (Journal of World Conference (JWC), 2020)
Quality of service in the business world is very important so that all consumer needs are met. Likewise with the world of land transportation which is always developing both in its type, size, and methods used in providing services. The Neat Transit Bus which operates in DKI Jakarta is one of the modes of mass transportation provided by the DKI Jakarta government to support the service needs of DKI Jakarta residents. Good transportation services will bring up a high level of customer satisfaction. The purpose of this study is to determine the dominant factors that influence the parameters of BRT passenger satisfaction in DKI Jakarta, to know the level of female consumer satisfaction with the quality of BRT services in DKI Jakarta. The research method used in this study is the CSI (Customer Satisfaction Index) by distributing questionnaires to respondents. From the research, the level of satisfaction of female customers in using the BRT public transportation facilities in the DKI Jakarta provincial government was 66%. Customer satisfaction criteria are in the Satisfied category.